Implication of plasma dispersion effect for controlling refractive index in microresonator - Ahmad Noorden, Ahmad Fakhrurrazi; Daud, Suzairi; Ali, Jalil (American Institute of Physics, 2017)
In this paper, the theoretical simulation of all-pass microring resonator is performed by considering the plasma dispersion effect. The plasma dispersion contributes in changing the refractive index and resonance wavelength by manipulating the carrier concentration in silicon waveguide. The system requires a sandwich design of silicon microring waveguide which comprise P and N-types silicon material. The depletion region is bounded in the ring resonator waveguide which affect the carrier concentration of the silicon material. The plasma dispersion effect formulation contributes to analyze the effect for applied voltage on effective index and absorption coefficient. The shift of resonance wavelength is analyzed with respect to the change of refractive index.